ANALISIS KANDUNGAN TIMBAL PADA MINUMAN SUSU CAIR KEMASAN KALENG DI TONDANO MENGGUNAKAN SPEKTROFOTOMETRI SERAPAN ATOM - Elsa Sangian; Abdon Saiya; Stefan Marco Rumengan (Program Studi Kimia, Fakultas MIPA, Universitas PGRI Banyuwangi, 2026)
Canned liquid milk is a popular product because it is convenient, readily available, and has a long shelf life. Cans have the potential to cause lead contamination, which poses a risk to consumer health. This study aims to determine the lead Pb content in canned liquid milk. The qualitative analysis method in this study used HCl reagent, while quantitative analysis employed Atomic Absorption Spectrophotometry on the three canned liquid milk samples labeled A, B, and C. Qualitative test results indicated that all three milk samples tested positive for Pb, as evidenced by the formation of a white precipitate. Quantitative analysis results showed Pb levels of 0.014 mg/kg in sample A, 0.008 mg/kg in sample B, and 0.007 mg/kg in sample C. All samples remained below the limit specified by SNI 8984 of 2021, which is 0.02 mg/kg.